Analisis reaksi pasar modal terhadap berbagai pengumuman kasus Covid-19 pada fase awal - Eka Yulianti; Ifan Wicaksana Siregar; Novi Susyani (Journal of Business & Banking, 2022)
The capital market is an investment place that is developing quite rapidly today. When investing in the capital market, investors are facing a trade off between return and risk. The purpose of this study is to analyze the reaction of the capital market to news related to the Covid-19 case in the early stages of the pandemic by using an event study, part of the theory of market efficiency. The announcements that were studied were the reactions: 1) Announcement of the initial appearance of Covid-19, 2). WHO announcement has declared Covid19 a global pandemic, 3). Announcement of spike in Covid-19 cases to reach 10,000. This study used stocks that join the LQ45 index as the population. Furthermore, the technique of determining the sample is a saturated sample. The results show that the capital market reacts to the 3 series of events studied. In addition, there is an abnormal return. This shows that the market is working efficiently in a semi-strong form. Furthermore, based on the paired sample T-test, there is no difference in TVA and transaction frequency before and after the event. For companies that are expected to develop strategies to minimize the occurrence of a significant decline in stock prices due to force majeure events. In terms of investors, this research provides information signals to them that force majeure events can affect market performance.